2012
DOI: 10.1056/nejmoa1203388
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Sugar-Sweetened Beverages and Adolescent Body Weight

Abstract: BACKGROUND Consumption of sugar-sweetened beverages may cause excessive weight gain. We aimed to assess the effect on weight gain of an intervention that included the provision of noncaloric beverages at home for overweight and obese adolescents. METHODS We randomly assigned 224 overweight and obese adolescents who regularly consumed sugar-sweetened beverages to experimental and control groups. The experimental group received a 1-year intervention designed to decrease consumption of sugar-sweetened beverages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
542
4
19

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 611 publications
(578 citation statements)
references
References 25 publications
13
542
4
19
Order By: Relevance
“…The smaller sample size of these studies (<300) compared with our study of more than 2000 older children may explain the conflicting observations as it increases the chance of type 2 errors. As well, our study, which shows that SSB intake is associated with greater fat mass accumulation in children transitioning into adolescence, is consistent with a recent well-designed randomized controlled trial conducted in overweight and obese adolescents who regularly consume SSB (44) . In that study, Ebbeling et al (44) found that those assigned to receive non-caloric beverage provisions for 1 year had smaller gains in BMI compared with those assigned to the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The smaller sample size of these studies (<300) compared with our study of more than 2000 older children may explain the conflicting observations as it increases the chance of type 2 errors. As well, our study, which shows that SSB intake is associated with greater fat mass accumulation in children transitioning into adolescence, is consistent with a recent well-designed randomized controlled trial conducted in overweight and obese adolescents who regularly consume SSB (44) . In that study, Ebbeling et al (44) found that those assigned to receive non-caloric beverage provisions for 1 year had smaller gains in BMI compared with those assigned to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…As well, our study, which shows that SSB intake is associated with greater fat mass accumulation in children transitioning into adolescence, is consistent with a recent well-designed randomized controlled trial conducted in overweight and obese adolescents who regularly consume SSB (44) . In that study, Ebbeling et al (44) found that those assigned to receive non-caloric beverage provisions for 1 year had smaller gains in BMI compared with those assigned to the control group. Interestingly, body fat did not relate to the experimental condition, but it was obtained by bioelectrical impedance (as opposed to DXA as in our study), which has been shown to inaccurately measure body fat in overweight individuals (45) .…”
Section: Discussionsupporting
confidence: 92%
“…Explanation (2) could be supported by previous observational studies suggesting an association between non-caloric sweeteners and consumption of artificially sweetened beverages and weight gain [25,26], although recent randomised trials conducted in children and adolescents do not support this hypothesis [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Beverage displacement changes towards more sweetened beverages have been previously documented in children in relation to weight management (26,27) . Overall, consumption of caloric sweetened beverages has been extensively linked with obesity and poor heath outcomes independently of energy intake, given their effect on satiety and insulin metabolism (28)(29)(30) . Given the nutritional and health implications associated with these beverages, the Beverage Consumption Recommendations for the Mexican Population encouraged the consumption of plain water as a first choice (750-2000 ml/d), followed by no/low calorie beverages with no sugar added and skimmed milk.…”
Section: Discussionmentioning
confidence: 99%